THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT MDR CONVECTION IN BANYUWANGI - Muhdar; Nely Supeni; Saiful Amin (STIE Mandala Jember, 2023)
This study aims to determine and analyze the effect of work motivation, work environment onemployee performance at MDR Convection in Banyuwangi. This study uses a type ofquantitative research.The independent variable is Work Motivation (X1), Work Environment(X2), and the dependent variable is Performance (Y2). Data analysis used is validity andreliability test, normality test, heteroscedasticity test, multicollinearity test, classical assumptiontest, , Multiple Linear analysis, t test and f test. The results of the t-test or partial test on multipleregression on the effect of work motivation on employee performance showed that there was nosignificant effect. This proves that the effect of low work motivation will not increase employeeperformance at the Banyuwangi Convection MDR. The results of the T-test or multipleregression partial test on the influence of the work environment on employee performance showthat there is no significant effect. This proves that the unfavorable work environment will notimprove employee performance at MDR Convection Banyuwangi. The results of the F test ormultiple regression simultaneous test on the effect of work motivation and work environment onemployee performance show results that have a significant effect. This proves that workmotivation and work environment improve employee performance at MDR ConvectionBanyuwangi.